2017
DOI: 10.1371/journal.pone.0184528
|View full text |Cite
|
Sign up to set email alerts
|

Development of hop transcriptome to support research into host-viroid interactions

Abstract: Viroids, the smallest known pathogens, unable to encode any proteins, can cause severe diseases in their host plants. One of the proposed mechanisms of their pathogenicity includes silencing the host’s genes via viroid-derived small RNAs, which are products of the host’s immune response to the viroid’s double stranded RNA. Humulus lupulus (hop) plants are hosts to several viroids; two of them, HLVd and CBCVd, are interesting models for studying host-viroid interactions, due to the symptomless infection of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 81 publications
(95 reference statements)
2
43
0
1
Order By: Relevance
“…The assemblies are also reasonably complete with more than 70% of BUSCO genes present on average. This is a similar distribution of BUSCO scores to those in the recently published 1KP project One Thousand Plant Transcriptomes Initiative, 2019) and other studies (Blande et al, 2017;Evkaikina et al, 2017;Pokorn et al, 2017;Weisberg et al, 2017) . Like many transcriptome assemblies (Johnson et al, 2012;Carpenter et al, 2019;Patterson et al, 2019) , these assemblies also contain a large number of small scaffolds (<300 bp).…”
Section: Discussionsupporting
confidence: 84%
“…The assemblies are also reasonably complete with more than 70% of BUSCO genes present on average. This is a similar distribution of BUSCO scores to those in the recently published 1KP project One Thousand Plant Transcriptomes Initiative, 2019) and other studies (Blande et al, 2017;Evkaikina et al, 2017;Pokorn et al, 2017;Weisberg et al, 2017) . Like many transcriptome assemblies (Johnson et al, 2012;Carpenter et al, 2019;Patterson et al, 2019) , these assemblies also contain a large number of small scaffolds (<300 bp).…”
Section: Discussionsupporting
confidence: 84%
“…The length-frequency distribution ( Figure 3A), N50, N75 value of de novo assembly, average GC content, and the average lengths of unigenes (Table 1), represents the broad view of all three unigene sets and combined transcriptomes. The comparison analysis showed that the N50 and the average length of unigenes derived from three libraries were much longer than those of any specific tissue and previous studies on hop (N50: 650 bp) [32], suggesting the high quality of sequencing data. Pearson's correlation coefficient between biological replicates were approximately 0.9, suggesting the high reproducibility across samples and credibility of RNA-seq results (Supplementary Materials Figure S1).…”
Section: Transcriptome Sequence Analysis and De Novo Assemblymentioning
confidence: 70%
“…In the present study, a total of 128 million clean reads were obtained after trimming and performing error corrections from the three distinct tissues, representing 12.94 Gb sequences were de novo assembled into a total of 43,550 unigenes ( Table 1). The number of transcripts and an average N50 length of assembled data was slightly higher than RNA-Seq reports of hop genome [32], indicating that sequencing data including transcriptomes were of high quality and integrity and could serve as a basis for functional gene studies and marker development in hop.…”
Section: Building a Transcriptome Resource And Gene Annotationmentioning
confidence: 83%
“…Zanj smo uporabili programski paket R (paket Rcmdr, različica 2.4-x). (Rahman et al, 2008;Pokorn et al, 2017).…”
Section: Materials In Metodeunclassified